PENGEMBANGAN MODUL MIKROBIOLOGI DAN PARASITOLOGI BERORIENTASI KONSTRUKTIVISME DI APIKES IRIS PADANG - Rahmi Septia Sari (Ensiklopedia of Journal, 2020)
The textbook used for microbiology and parasitology lectures at Apikes Iris has not been able to construct student knowledge. Students need a lecture material that can help and facilitate them in lectures and can increase learning activities and motivation, therefore it is necessary to develop lecture materials in other forms namely constructivism-oriented microbiology and parasitology modules which are practical and effective for microbiology and parasitology lectures in Apikes Iris. This research is a development study using 4D models. the steps taken are define, design, and develop. In the define stage, syllabus analysis is conducted, interviews with lecturers, and student analysis. At the design stage, module design is carried out. The develop phase consists of the validation, practicality, and disseminate stages consisting of effectiveness testing. After being designed the module was validated by experts and practitioners then it was tested limitedly to Apikes Iris level one students to be exact local B to know the practicality and effectiveness of the module. Based on the results of research conducted, it is known that the learning module is in very valid criteria, namely the contents of the module are in accordance with established competency standards. The module is very practical, seen from the implementation of lectures that have been according to plan and time efficiency. The module instructions are clear, the contents of the module are in accordance with the needs of students and the module has been effective, shown by increased activity, motivation, and student learning outcomes.